Together throughout the year: seasonal patterns of bacterial and eukaryotic microbial communities in a macrotidal estuary - Vincent Hervé; Jérôme Morelle; Josie Lambourdière; Pascal Jean Lopez; Pascal Claquin (Environmental Microbiome)
Abstract Background Estuaries are complex ecosystems linking river and marine environments, where microorganisms play a key role in maintaining ecosystem functions. In the present study, we investigated monthly 8 sites at two depth layers and over a one-year period the bacterial and eukaryotic community dynamics along the Seine macrotidal estuary (Normandy, France). To date, the taxonomy of the microbial diversity present in this anthropized estuary remains elusive and the drivers of the microbial community structure are still unknown. Results The metabarcoding analysis of 147 samples revealed both a high bacterial and eukaryotic diversity, dominated by Proteobacteria, Bacteriodota, Actinobacteriota and Bacillariophyta, Spirotrichea, Dinophyceae, respectively. Along the estuary we only detected significant spatial patterns in the bacterial and eukaryotic community compositions for three and two months out of twelve, respectively. However, we found a clear seasonal effect on the diversity of both microbial communities driven by physical and chemical variables that were fluctuating over the year (temperature, irradiance, river flow). Biotic associations were also significant drivers of both alpha and beta diversity. Throughout the year, we identified a diverse and abundant core microbiota composed of 74 bacterial and 41 eukaryotic OTUs. These regionally abundant species include habitat generalists encompassing heterotrophs, phototrophs and consumers. Yet, many of these core OTUs remain taxonomically and functionally poorly assigned. Conclusions This molecular survey represents a milestone in the understanding of macrotidal estuary dynamics and the Seine ecosystem, through the identification of putative markers of ecosystem functioning. It also identifies seasons and biotic associations as main drivers of the Seine estuary microbiota and reveals the importance of a core microbiota throughout the year.